Nestl? entangled : braving the Maggi noodle crisis in India - Kaul, Asha; Chaudri, Vidhi; Vankar, Niharika (London : Indian Institute of Management, Ahmedabad, 2016)
The case describes the Maggi debacle faced by Nestle in India. On May 21, 2015, the Food and Drug Administration (FDA) ordered Nestle India to recall Maggi after confirming presence of high levels of lead and Mono Sodium Glutamate (MSG) in the product. The case traces the events in the Maggi crisis and deliberates on the reputational loss as evidenced in the boycott of the product, sagging top and bottom line of the company, mounting consumer hostility and loss of faith and trust in leadership. As the events unfold the reader is able to discern the challenges that confront organisations in a crisis situation, and reflect on Nestle's crisis management strategies. The case provokes the reader to deliberate on the aftermath of the recall. Will Nestle be able to get Maggi back on the shelf? Will they ever be able to recapture consumer faith and trust? Will the Indian market be willing to forgive and forget? Would the company be able to regain consumer faith, change public perceptions and recapture mind space? If yes, how?
Originally published in Kaul, A., Chaudri, V., & Vankar, N. (2016). Nestl? entangled: Braving the Maggi noodle crisis in India. COMM0013. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nestl?.; Consumer satisfaction -- India -- Case studies; Monosodium glutamate -- India -- Case studies